Novel mode of 2-fold interpenetration observed in a primitive cubic network of formula [Ni(1, 2-bis(4-pyridyl)acetylene)2(Cr2O7)]n. Issue 80 (26th August 2015) - Scott, Hayley S.; Bajpai, Alankriti; Chen, Kai-Jie; Pham, Tony; Space, Brian; Perry, John J.; Zaworotko, Michael J.
Abstract : A novel mode of inclined interpenetration in a primitive cubic network affords 1D ultramicropores that provide insight into gas sorption of CO2 . Abstract : A primitive cubic (pcu ) network of formula [Ni(1, 2-bis(4-pyridyl)acetylene)2 (Cr2 O7 )] n, DICRO-2-Ni-i, has been synthesised and found to exhibit a novel type of inclined 2-fold interpenetration and an isosteric heat of adsorption ( Q st ) of 30.5 kJ mol −1 towards CO2 at zero loading. Q st is relatively high in the broad context but less than that observed in related hybrid ultramicroporous materials, a feature that can be understood after studying pore structure and molecular simulations of CO2 adsorption.